Study on the Restoration of Ecological Environments in Mining Area Based on GIS Technology - Qi, Jiawei; Zhang, Yichen; Zhang, Jiquan; Wu, Chenyang; Chen, Yanan; Cheng, Zhongshuai (Sustainability, 2023)
Taking Erdaojiang and Dongchang District of Tonghua City, Jilin Province as examples, this paper studies the ecological environment restoration and governance model of their mining areas. In this paper, the vegetation cover (NDVI) data in the past ten years were selected from the study area. The Theil–Sen median and Mann–Kendall (MK) methods were used to analyze the time series of NDVI, and the vegetation cover change trend map of the study area was obtained. Then, the land use data of the study area for 4 years were selected, and the transfer matrix method was used to analyze the land use conversion between the years. Finally, according to the characteristics of the distribution of mines in the study area, for the mining area in different natural geographical locations, it was concluded that the restoration of cultivated land and the restoration of forest land and ecological reconstruction were adopted. Among them, the restoration of forest land includes natural restoration and artificial intervention.